Industrial Parks in the System of Investment Security of the State: Theory and Practice (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyzes the problem of creating and organizing the activity of industrial parks as an instrument for supporting the development of small and medium-sized enterprises, and intensifying the investment activity of the state with a view to its economic growth.  The importance of industrial parks in modern economic conditions is analyzed.  The preconditions and the main stages of creation of industrial parks in Ukraine are revealed. The basic and competitive features of industrial parks, conditions and benefits from investment of each participant of the project are determined. The world experience in the development and functioning of industrial parks is considered. The legal base, possible financing conditions and directions of state support of industrial parks are analyzed. The concrete examples of the creation of industrial parks in separate regions of Ukraine are considered, the advantages and disadvantages of the data of special investment regimes are determined.  The proposals, the implementation of which will contribute to increasing the efficiency of the functioning of industrial parks and ensuring their positive impact on the development of the national economy. It’s determined that the creation of industrial parks contributes to the improvement of the investment climate, the implementation of a range of innovative opportunities and ensuring a healthy competitive environment for doing business. Industrial parks today give a chance to carry out a serious technological revolution in Ukraine, attract «smart» investments, which will be aimed at technology and modernization of the national commodity producer. The main results of the creation of industrial parks in Ukraine can be: attraction of investments; increase of tax revenues to the budget; creating new jobs; creation of environmentally friendly industrial production; inhibition of educational and labour migration of the population and others.
Keywords: state support, industrial park, investments, investment security, region, strategic development